2006
DOI: 10.1007/s11306-006-0028-0
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipid capture combined with non-linear chromatographic correction for improved serum metabolite profiling

Abstract: Serum analysis with LC/MS can yield thousands of potential metabolites. However, in metabolomics, biomarkers of interest will often be of low abundance, and ionization suppression from high abundance endogenous metabolites such as phospholipids may prevent the detection of these metabolites. Here a cerium-modified column and methyl-tert-butyl-ether (MTBE) liquid-liquid extraction were employed to remove phospholipids from serum in order to obtain a more comprehensive metabolite profile. XCMS, an in-house devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…3). At the end, standard sample of lysoPC and the literature from Want et al (2006) and Wang et al (2005) was used to confirm the result. It has been seen from Table 2 that seven potential biomarkers are identified according to the method described above.…”
Section: Resultsmentioning
confidence: 99%
“…3). At the end, standard sample of lysoPC and the literature from Want et al (2006) and Wang et al (2005) was used to confirm the result. It has been seen from Table 2 that seven potential biomarkers are identified according to the method described above.…”
Section: Resultsmentioning
confidence: 99%
“…They found that cold methanol was the optimal compromise for most extracted metabolites and the best protein depletion. In a subsequent work, the same group showed that removal of phospholipids by means of selective capture unmasked other low abundant metabolites (Want et al 2006b). For analyses utilizing GC-MS, it is typically necessary to chemically derivatize polar and non-volatile analytes.…”
Section: Sample Preparationmentioning
confidence: 96%
“…Mass spectrometry (MS)-based metabonomic studies have been performed in order to determine qualitative and quantitative differences between the endogenous metabolite pools of study groups [1][2][3][4][5][6][7][8][9][10][11][12]. Most matrices, such as plasma, serum, and cerebral spinal fluid, are physiologically controlled [13][14][15][16]; however, urine volumes can vary widely based upon water consumption and other physiological and pathophysiological factors, and, as a result, the concentrations of endogenous metabolites in urine also vary.…”
Section: Introductionmentioning
confidence: 99%